SPR741, Double- or Triple-Combined With Erythromycin and Clarithromycin, Combats Drug-Resistant Klebsiella pneumoniae, Its Biofilms, and Persister Cells - She, Pengfei; Liu, Yaqian; Xu, Lanlan; Li, Yimin; Li, Zehao; Liu, Shasha; Hussain, Zubair; Wu, Yong (Frontiers in Cellular and Infection Microbiology, 2022)
Klebsiella pneumoniae has emerged as a major clinical and public health threat owing to the increasing prevalence of healthcare-associated infections caused by multidrug-resistant or extensively drug-resistant strains. However, increasing antibiotic resistance and the absence of clinically effective antimicrobial agents make combination therapy an urgent need. This study investigated the anti-microbial activity of SPR741, a polymyxin B derivative, in combination with macrolide antibiotics (erythromycin and clarithromycin), against K. pneumoniae and its extensively drug-resistant and pandrug-resistant clinical isolates. Monotherapy, double, and triple combination therapies were performed to identify the most effective treatment combination using in vitro checkerboard, time-killing kinetics. Furthermore, we evaluated the biofilm eradication and persister cell-killing activity of these combinations using laser confocal microscopy and colony forming unit counting. In addition, a neutropenic mouse thigh infection model was used to assess the therapeutic efficacy and toxicity of the triple antibiotic combination against pandrug-resistant K. pneumoniae in vivo. Our results suggested that SPR741 combined with macrolides exhibited strong synergistic bactericidal activity against extensively drug-resistant and pandrug-resistant K. pneumoniae. These antibiotic combinations could also effectively eradicate highly resistant biofilms and kill bacterial cells embedded in the biofilms of K. pneumoniae. SPR741-based double or triple combinations could also effectively kill K. pneumoniae persister cells in vitro and demonstrated considerable efficacy and low toxicity in a neutropenic mouse thigh infection model in vivo. In summary, our findings indicated that SPR741, in combination with macrolide antibiotics (double or triple combination), has the potential to serve as a novel treatment option against extensively drug-resistant and pandrug-resistant K. pneumoniae -related infections.